Faktor Risiko Helminthiasis pada Domba di Kecamatan Panjatan, Kabupaten Kulon Progo, Provinsi D.I. Yogyakarta, Indonesia: Risk Factors associated with Helminthiasis in Sheeps in Panjatan District, Kulon Progo Regency, D.I. Yogyakarta Province, Indonesia) - Dewi, Dias Aprita; Pramu, Pramu; Widiarso, Budi Purwo; Nugraheni, Yudhi Ratna; Awaludin, Aan (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2026)
Background: Small ruminant infections with helminthiasis cause acute or chronic gastrointestinal problems and significant global economic losses. Purpose: The present study aimed to determine the prevalence and risk factors of helminthiasis in sheeps in Panjatan district, Kulon Progo regency, D.I. Yogyakarta province, Indonesia. Methods: This study was conducted in Bugel Village, Depok, and Krembangan, Panjatan Subdistrict, Kulon Progo Regency, Special Region of Yogyakarta, Indonesia. Fecal samples (n = 176) were collected from 17 farms and examined for the presence of helminth eggs using the Gordon–Whitlock method, followed by quantitative determination of eggs per gram (EPG) of feces. The number of positive samples relative to the total number of samples was used to calculate prevalence.The association between helminthiasis prevalence and risk factors, including intrinsic factors (sex, age, and breed) and extrinsic factors (flooring system, housing type, housing hygiene, and grazing system), was analyzed. The relationships were assessed using the chi-square (χ²) test. A p-value of 0.05 or less was considered statistically significant (P ≤ 0.05). Results: The identified helminth eggs were nematode Strongyle type eggs, nematode eggs Trichuris sp, and cestode eggs Moniezia spp. The univariate analysis result of risk factors indicated that age, type of pen, pen management, and pen cleaning were associated with helminthiasis (P≤0.05). Conclusion: Finally, prevalence observed in this study was high, and significant associations were identified between age, flooring system, housing type, and housing hygiene and the occurrence of helminthiasis in sheep from Panjatan Subdistrict, Kulon Progo Regency, Special Region of Yogyakarta, Indonesia. Effective management and hygiene practices should be implemented based on identified risk factors to prevent the disease. Further studies on the level of pathogenicity and its economic impact on livestock production are needed to better support the success of helminthiasis control programs.